Effects of Lightning Electromagnetic Field due to Lightning Strikes on a Tall Structure - Ir. Ts. Dr. Norhidayu Rameli; Mohd Zainal Abidin Abd Kadi; Mahdi Izadi; Norhafiz Azis (UiTM Press, 2024)
Indexed by Scopus